СТРУКТУРНІ ЗМІНИ ЕНЕРГОСИСТЕМ ТА ВІДПОВІДНІ ЗМІНИ ЇХНІХ ДИНАМІЧНИХ ВЛАСТИВОСТЕЙ - Буткевич, О.Ф.; Гурєєва, Т.М.; Юнєєва , Н.Т. (Інститут електродинаміки НАН України, Київ, 2023)
Study results concerning the changes in the power systems (PS) dynamic properties as a result of the electrical networks' development and a significant increase of the share of distributed sources of generation in the structure of generating capacities of the PS are presented. With the use of three developed PS models which corresponded to successive stages of the PS development, as a result of information processing about electromechanical transient processes, the changes in the spectrum of PS natural frequencies as well the changes of the emergency processes' course were revealed. The obtained results make it possible to predict qualitative changes of dynamic properties of the Interconnected Power System of Ukraine at the stages of its post-war recovery and development. References 10, figures 10, tables 3.